Toward risk-based aviation security policy - Robert W. Poole (Organisation for Economic Co-operation and Development (OECD), Joint Transport Research Centre (JTRC), 2008)
The well-coordinated terrorist attacks on Sept. 11, 2001 presented the world with a new aviation security threat: the capture of aircraft in flight to be used as human-guided missiles. The two previous threats - hijacking an aircraft for ransom and putting a bomb aboard an aircraft - had led to varying degrees of screening of baggage and passengers in developed countries, plus some use of on-board security personnel on selected flights in some countries. In the wake of 9/11, governments in the United States, Canada, and Europe (at both national and EU levels) implemented a number of additional aviation security measures, among them: - strengthened (and locked) cockpit doors; - 100% screening of checked baggage; - more thorough screening of passengers and their carry-on baggage; - increased use of on-board security officers; - increased attention to air cargo; - and greater attention to airport access control and perimeter control. (...)
Keywords: 330